ANALISIS KESULITAN BELAJAR PESERTA DIDIK DENGAN KEMAMPUAN LITERASI RENDAH (Studi kasus kesulitan belajar akademik di kelas V SDN Cibaregbeg Semester Gasal Tahun Ajaran 2021/2022) - Yunira Putri Pangestu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research uses case study research with a qualitative approach. The purpose of this study was to determine the learning difficulties of students with low literacy skills at SDN Cibaregbeg, Sukabumi Regency in 2021/2022. The subject studied in this study was one of the students in the fifth grade at SDN Cibaregbeg, Sukabumi Regency. Data collection and data recording were carried out through procedures such as observation, interviews, and documentation. The data analysis technique used in this study is the data reduction, data presentation, and verification (conclusion) stages. To obtain the results of the study which looked at the learning difficulties of students with low literacy skills at SDN Cibaregbeg, the researchers used credibility, transferability, dependability, and confirmability tests which showed that the factors causing learning difficulties in students with low literacy skills were internal and external factors. Students do not have good learning motivation and have low interest in reading so that students experience learning difficulties, especially in learning to read. Efforts that can be made to deal with the problem of learning difficulties is to encourage students to study regularly both at home and at school. Another thing that can be done is to motivate students not to forget the benefits of learning by providing interesting learning.